Irrigation water requirements of rice using Cropwat model in Northern Benin. - Bouraima, Abdel-Kabirou; Zhang, Weihua; Wei, Chaofu (International Journal of Agricultural and Biological Engineering, 2015)
Understanding crop water requirements (CWR) in semi-arid region is essential for better irrigation practices, scheduling and efficient use of water since the water supply through rainfall is limited. This paper estimated the crop reference and actual evapotranspiration (Eto and ETc) respectively and the irrigation water requirement of rice (Oryza sativa L.) in Benin’s sub-basin of Niger River (BSBNR) of west Africa, using CROPWAT model. The long recorded climatic data, crop and soil data from 1942 to 2012 were computed with the Cropwat model which is based on the United Nations’ Food and Agriculture Organization (FAO) paper number 56 (FAO56). The Penman-Monteith method was used to estimate ETo. Crop coefficients (Kc) from the phenomenological stages of rice were applied to adjust and estimate the actual evapotranspiration ETc through a water balance of the irrigation water requirements (IR). The results showed the BSBNR annual reference evapotranspiration (ETo) was estimated at 1 967 mm. The lowest monthly value of ETo of 123 mm, was observed in August month, middle of the rainy season while the highest value 210 mm was observed in March within dry season. The crop evapotranspiration ETc and the crop irrigation requirements were estimated at 651 mm and 383 mm, respectively in rainy season and 920 mm and 1 148 mm, respectively within a dry season. Irrigation projects of these seasons can then be scheduled for water use efficiency based on these findings.Keywords: crop evapotranspiration, irrigation water requirement, rice, CROPWAT, model, BeninDOI: 10.3965/j.ijabe.20150802.1290